Pertanggung Jawaban Pidana Pengguna Jasa Prostitusi Online Anak Menurut Hukum Positif Indonesia - Erlangga Bagus Setiyawan; Taun Taun (Peneliti.net, 2023)
Prostitution is an activity that has a very long history in human civilization. Along with the times, today's prostitution activities also adjust to the development of information and communication technology which makes prostitution activities increasingly difficult to limit. Prostitution activities are only regulated in the Criminal Code which can only be imposed on pimps. Meanwhile, other parties such as users and providers of prostitution services who are involved in these activities have not yet received legal regulations that can ensnare them. Penalties regulated in the Criminal Code and the Law define punishment only for service providers or pimps. The Criminal Code and the Law do not regulate the provisions for sentencing service users for online prostitution crimes. This study aims to discuss criminal responsibility for users of online prostitution services for minors and to find out criminal responsibility for children who distribute information containing prostitution. This research method is normative research.